The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/tox.23156
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin protects against the chlorpyrifos‐induced chronic hepato‐renal toxicity in rats associated with oxidative stress, inflammation, apoptosis, autophagy, and up‐regulation of PARP‐1/VEGF

Abstract: In this study, we investigated the effects of hesperidin (HSP) on oxidants/antioxidants status, inflammation, apoptotic, and autophagic activity in hepato-renal toxicity induced by chronic chlorpyrifos (CPF) exposure in rats. We used a total of 35 male albino rats in five groups of seven: control, HSP 100, CPF, CPF + HSP50, and CPF + HSP100. After rats were sacrificed, blood, liver, and kidney samples were collected.Serum levels of aspartate aminotransferases (ALT and AST), alkaline phosphatase (ALP), creatini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 71 publications
9
26
0
1
Order By: Relevance
“…Endogenous FoxO1 is a key regulator of autophagy in neurons (Vidal et al., 2012 ). In addition, studies have shown that Beclin‐1 may be involved in the activation of Caspase‐3 (Küçükler et al., 2021 ). Bcl‐2 negatively regulates autophagy by inhibiting Bax and blocking Beclin‐1 (Lindqvist et al., 2014 ), indicating that there is mutual crosstalk between autophagy and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous FoxO1 is a key regulator of autophagy in neurons (Vidal et al., 2012 ). In addition, studies have shown that Beclin‐1 may be involved in the activation of Caspase‐3 (Küçükler et al., 2021 ). Bcl‐2 negatively regulates autophagy by inhibiting Bax and blocking Beclin‐1 (Lindqvist et al., 2014 ), indicating that there is mutual crosstalk between autophagy and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…SA-mediated increase in kidney 8-OHdG was reduced upon treatment with hesperidin, thereby exerting nephroprotective effects [ 89 ]. Hesperidin reduces CPF-induced hepatorenal toxicity by reducing 8-OHdG levels and regulating PARP/VEGF genes at biochemical, cellular, and molecular levels [ 90 ]. Similarly, AA intoxication can significantly increase 8-OHdG, while administration of hesperidin improves the concentration and activities of antioxidant biomarkers and decreases the expression level of 8-OHdG in kidney tissue [ 91 ].…”
Section: Nephroprotective Effects Of Flavonoidsmentioning
confidence: 99%
“…Administration of doses 1 and 10 mg/kg showed no significant improvement, while 75, 100, and 150 mg/kg showed significant inhibition of cell death, inflammation, and oxidative stress in kidney injury models [ 73 , 74 , 75 , 76 , 77 ]. Hesperidin was administered at five different doses (10, 25, 50, 100, and 200 mg/kg) [ 89 , 90 , 91 , 117 , 118 , 119 ]. All doses affected protein and mRNA expression levels of TNF-α, IL-1β, NF-κB, SOD, MDA, and GSH.…”
Section: Pharmacokinetics and Nephroprotective Effects Of Flavonoidsmentioning
confidence: 99%
“…Moreover, it was observed that decreased GSH levels probably caused a further increase in ROS levels and that these aggressive molecules damaged the membranes of lung tissue cells, causing lipid peroxidation, thereby increasing MDA levels. Previous studies have reported that different flavonoids applied against various pesticide groups alleviate oxidative stress and alleviate the toxic effects of these compounds [31,32]. In our study, it was determined that RUT treatment suppressed oxidative stress by providing the regeneration of GSH, whose levels were significantly reduced by MLT, and by preventing lipid peroxidation.…”
Section: Discussionmentioning
confidence: 62%